Preparation method and application of anti-aging water-based adhesive
By combining modified fiber resin and montmorillonite solution, sodium alginate, calcium chloride and surfactant, aqueous glue is formed, which solves the problem of degraded bonding performance and insufficient sealing properties of aqueous glue in humid environments, and achieves the goal of achieving It improves water resistance and sealing properties, and shortens drying time under high humidity conditions, making it suitable for wet and rapid processing production processes.
Patent Information
- Application Number
- CN202411078953.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2024-12-13
AI Technical Summary
The existing water-based glue has degraded bonding performance, insufficient sealing properties and excessive drying time in humid environments, which limits its application in wet or rapid processing production processes.
By preparing modified fiber resin and modified montmorillonite solution, combining sodium alginate, calcium chloride, dodecyl trimethylammonium bromide and sodium dodecyl sulfate, a homogeneous network structure was formed and tannins were used. Acid and chitosan accelerate curing, improving the water resistance, sealing and drying speed of aqueous glue.
It significantly improves the water resistance and sealing properties of water-based glue, is suitable for humid environment applications, and shortens drying time under high humidity or low temperature conditions, extends service life and improves adhesive performance.
Smart Images

Figure CN119119955A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water-based adhesive preparation, and in particular to a method for preparing an aging-resistant water-based adhesive and application thereof. Background Art
[0002] Water-based adhesive is an environmentally friendly adhesive, the main component of which is water, which can replace toxic organic solvents. It uses natural or synthetic polymers as adhesives and water as solvent or dispersant. It contains a small amount of solvent to control viscosity or fluidity, but it is not 100% solvent-free and will be accompanied by certain volatile organic compounds and a slight smell.
[0003] Patent No. CN109897582A discloses a method for preparing an aging-resistant sealant. The high temperature resistance and aging resistance of the sealant prepared by the present invention are further improved. The montmorillonite is organically treated by a cation exchange method to change the montmorillonite from hydrophilic to lipophilic. The modified montmorillonite treated with hexadecyltrimethylammonium bromide has good compatibility with phenolic resin. The modified montmorillonite is bonded to the phenolic resin to improve the crosslinking density, which has broad application prospects.
[0004] After searching the above patents, it was found that the water-based glue has the following shortcomings: 1. The polymer components in the water-based glue may soften or decompose after contacting water, resulting in a decrease in bonding performance. This feature makes the water-based glue unsuitable for use in humid environments or applications involving contact with water; 2. Although montmorillonite modified with hexadecyltrimethylammonium bromide has good compatibility, it is impossible to further increase the sealing of the water-based glue while ensuring good compatibility, which affects the waterproof and air-proof effect of the water-based glue; 3. When the existing water-based glue is dried and solidified, the evaporation rate of water is slow, especially in high humidity or low temperature environments, and the drying time of the water-based glue will be significantly extended. This feature limits the application of water-based glue in certain production processes that require rapid processing.
[0005] Therefore, a method for preparing an aging-resistant water-based adhesive and its application are proposed to solve the above problems. Summary of the invention
[0006] The main purpose of the present invention is to provide a method for preparing an aging-resistant water-based adhesive with strong water resistance, high sealing performance, durable aging resistance and fast drying speed, which is applied to the preparation of aging-resistant water-based adhesive.
[0007] To achieve the above object, the technical solution adopted by the present invention is: an aging-resistant water-based adhesive, the preparation method of which is specifically as follows: Step 1: Prepare modified fiber resin, grind wheat straw for 25 to 35 minutes, mix with 20% by mass sodium hydroxide solution, heat to 65 to 75°C, keep warm and soak for 60 to 80 minutes, add malic acid solution and mix, collect filter residue, add modified material, obtain modified fiber resin, and set aside; Step 2: preparing a modified montmorillonite solution, mixing montmorillonite and distilled water, stirring for 1 to 2 hours, adding 3% to 5% of dodecyltrimethylammonium bromide by mass of montmorillonite, and then adding sodium dodecyl sulfate, stirring to obtain a modified montmorillonite solution for later use; Step 3: Mixing reaction, pour the modified fiber resin and modified montmorillonite solution into a reactor with a stirrer, heat to 100 to 120°C, pour in tannic acid and chitosan, stir and react for 45 to 55 minutes, and discharge the material to obtain aging-resistant water-based adhesive.
[0008] The specific preparation method of the modified fiber resin is: (1) After washing the wheat straw with distilled water for 1 to 2 times, the wheat straw is put into a grinder and ground for 25 to 35 minutes to obtain a wheat straw grind. The wheat straw grind is mixed with a sodium hydroxide solution having a mass fraction of 20%, and the mixture is put into a reactor, heated to 65 to 75° C., and soaked for 60 to 80 minutes to obtain an alkali-soaked product. (2) mixing the alkali-leached product with 8% malic acid solution by mass, placing the product in a high-temperature and high-pressure cooking tank, cooking the product for 2 to 3 hours, discharging the product, filtering the product, removing the filtrate, and collecting the residue; (3) The filter residue, phenol and 6% by mass sodium hydroxide solution are mixed and placed in a vacuum distillation apparatus for 50 to 60 minutes of vacuum distillation. 1% to 3% of a modified material is added to obtain a modified fiber resin.
[0009] The modified materials are sodium alginate solution and calcium chloride, and the weight ratio of the sodium alginate solution, calcium chloride and wheat straw is 3: (0.1 to 0.5): 1.
[0010] The specific steps of preparing the modified montmorillonite solution are as follows: Step 1, stirring at a constant temperature for 1 to 2 hours, and adding 3% to 5% of the mass of montmorillonite dodecyltrimethylammonium bromide during the stirring process, and then adding sodium dodecyl sulfate. After the stirring is completed, standing for 4 to 5 hours to obtain a mixed solution; Step 2: Filter the mixed solution, remove the filtrate, collect the filter residue, rinse the filter residue with distilled water for 2 to 3 times, filter under reduced pressure, collect the filtered filter residue, put the filtered filter residue into an oven and dry it to constant weight, then put it into a grinder and grind it for 30 to 40 minutes. After grinding, sieve it to obtain a modified montmorillonite solution.
[0011] The mixed mass ratio of the modified fiber resin and the modified montmorillonite solution is 2:1.
[0012] In the specific preparation of the modified fiber resin, the mixing mass ratio of the crushed wheat straw and the sodium hydroxide solution with a mass fraction of 20% is 1:6.
[0013] The high temperature and high pressure cooking temperature in the modified fiber resin is 185-195°C, the pressure is 1.9-2.1MPa, and the mass ratio of the alkali leaching material to the malic acid solution is 1:8; The mixed mass ratio of the filter residue, phenol and 5% sodium hydroxide solution in the modified fiber resin is 3:2:9.
[0014] The mixed mass ratio of dodecyltrimethylammonium bromide and sodium dodecyl sulfate in the modified montmorillonite solution is 1 to 1.2:1.1 to 1.3.
[0015] The weight ratio of each component of the aging-resistant water-based adhesive is composed of the following: 20% to 40% of modified fiber resin, 20% to 40% of modified montmorillonite solution, 6% to 10% of sodium hydroxide solution, 3% to 6% of malic acid solution, 2% to 8% of modified material, 0.5% to 3% of dodecyltrimethylammonium bromide, 1% to 3% of sodium dodecyl sulfate, 0.1% to 2% of tannic acid, and 0.1% to 2% of chitosan.
[0016] The aging-resistant water-based adhesive is used for bonding polyurethane semi-rigid foam, polypropylene sheet, sponge cloth, non-woven cloth, PVC cloth, leather or synthetic leather.
[0017] The present invention has the following beneficial effects: 1. In the present invention, by preparing a modified fiber resin, mixing wheat straw with sodium alginate, and adding calcium chloride after mixing, the polymer component in the prepared water-based glue can significantly increase the water resistance of the water-based glue through the combination of wheat straw and sodium alginate after meeting water, further increasing the bonding performance of the water-based glue, and by adding calcium chloride, the water stability of the sodium alginate-based material is improved, further improving the water resistance of the water-based glue and extending the service life of the water-based glue.
[0018] 2. In the present invention, by mixing dodecyltrimethylammonium bromide with sodium dodecyl sulfate, dodecyltrimethylammonium bromide has good solubility, heat resistance and surface activity. At the same time, dodecyltrimethylammonium bromide is mixed with carrageenan to form a uniform and tight network structure in the water-based glue, which effectively improves the sealing performance of the water-based glue. The prepared water-based glue can further increase the sealing performance of the water-based glue while ensuring good compatibility, thereby improving the waterproof and air-proof effect of the water-based glue.
[0019] 3. In the present invention, by combining carrageenan with tannic acid, the rapid curing effect of the water-based glue is increased, and by combining tannic acid with chitosan, the prepared water-based glue can increase the curing speed of the glue more quickly, and at the same time enhance the long-term durability of the glue, so that it can maintain good bonding properties under various environmental conditions, especially in wet or underwater environments. This feature can reduce the limitations of the application of water-based glue in certain production processes that require rapid processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention is a schematic diagram of the overall process of a method for preparing an aging-resistant water-based adhesive and its application. DETAILED DESCRIPTION
[0021] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0022] Comparative Example An aging-resistant water-based adhesive, the preparation method of which comprises the following steps: Step 1: grind the wheat straw for 25 to 35 minutes, mix it with a 20% sodium hydroxide solution by mass, heat it to 65 to 75°C, keep it warm and soak it for 60 to 80 minutes, add malic acid solution and mix it, collect the residue, and obtain the fiber resin for later use; Step 2: preparing a montmorillonite solution, mixing montmorillonite and distilled water, stirring for 1 to 2 hours, adding 3% to 5% of the mass of montmorillonite hexadecyltrimethylammonium bromide, stirring to obtain a montmorillonite solution for later use; Step 3: Mixing reaction, pour the fiber resin and montmorillonite solution into a reactor with a stirrer, heat to 100 to 120°C, stir and react for 45 to 55 minutes, and discharge the material to obtain the aging-resistant water-based adhesive.
[0023] The comparative example is a preparation step of the prior art for preparing a semi-finished aging-resistant water-based adhesive. The comparative example is compared with Example 1, Example 2 and Example 3. The comparison results are as follows: the comparative example lacks sodium alginate and calcium chloride compared with Example 1, the comparative example lacks dodecyltrimethylammonium bromide and sodium dodecyl sulfate compared with Example 2, and the comparative example lacks tannic acid and chitosan compared with Example 3.
[0024] Example 1 Please refer to Figure 1 As shown: A method for preparing an aging-resistant water-based adhesive and its application, comprising the following steps: Step 1: Prepare modified fiber resin, grind wheat straw for 25 to 35 minutes, mix with 20% by mass sodium hydroxide solution, heat to 65 to 75°C, keep warm and soak for 60 to 80 minutes, add malic acid solution and mix, collect filter residue, add modified material, obtain modified fiber resin, and set aside; Step 2: preparing a montmorillonite solution, mixing montmorillonite and distilled water, stirring for 1 to 2 hours, adding 3% to 5% of the mass of montmorillonite hexadecyltrimethylammonium bromide, stirring to obtain a montmorillonite solution for later use; Step 3: Mixing reaction, pour the modified fiber resin and montmorillonite solution into a reactor with a stirrer, heat to 100 to 120°C, stir and react for 45 to 55 minutes, and discharge the material to obtain the aging-resistant water-based adhesive.
[0025] The specific preparation method of the modified fiber resin is: (1) After washing the wheat straw with distilled water for 1 to 2 times, the wheat straw is put into a grinder and ground for 25 to 35 minutes to obtain a wheat straw grind. The wheat straw grind is mixed with a sodium hydroxide solution having a mass fraction of 20%, and the mixture is put into a reactor, heated to 65 to 75° C., and soaked for 60 to 80 minutes to obtain an alkali-soaked product. (2) mixing the alkali-leached product with 8% malic acid solution by mass, placing the product in a high-temperature and high-pressure cooking tank, cooking the product for 2 to 3 hours, discharging the product, filtering the product, removing the filtrate, and collecting the residue; (3) The filter residue, phenol and 6% by mass sodium hydroxide solution are mixed and placed in a vacuum distillation apparatus for 50 to 60 minutes of vacuum distillation. 1% to 3% of a modified material is added to obtain a modified fiber resin.
[0026] The modified materials are sodium alginate solution and calcium chloride, and the weight ratio of the sodium alginate solution, calcium chloride and wheat straw is 3: (0.1 to 0.5): 1.
[0027] The specific steps for preparing the modified montmorillonite solution are as follows: Step 1, stirring at a constant temperature for 1 to 2 hours, and adding 3% to 5% of the mass of montmorillonite dodecyltrimethylammonium bromide during the stirring process, and then adding sodium dodecyl sulfate. After the stirring is completed, standing for 4 to 5 hours to obtain a mixed solution; Step 2: Filter the mixed solution, remove the filtrate, collect the filter residue, rinse the filter residue with distilled water for 2 to 3 times, filter under reduced pressure, collect the filtered filter residue, put the filtered filter residue into an oven and dry it to constant weight, then put it into a grinder and grind it for 30 to 40 minutes. After grinding, sieve it to obtain a modified montmorillonite solution.
[0028] The mixed mass ratio of the modified fiber resin and the modified montmorillonite solution is 2:1.
[0029] Through the above-mentioned ratio, the preparation of the aging-resistant water-based adhesive in Example 1 and the comparative example has the following advantages: the combination of wheat straw and sodium alginate can significantly increase the water resistance of the water-based adhesive, prevent the water-based adhesive from softening or decomposing after contacting water, and further increase the bonding performance of the water-based adhesive. This feature makes the water-based adhesive suitable for use in humid environments or applications in contact with water. By adding calcium chloride, the water stability of the sodium alginate-based material is improved, and the water resistance of the water-based adhesive is further improved.
[0030] Example 2 Please refer to Figure 1 As shown: A method for preparing an aging-resistant water-based adhesive and its application, comprising the following steps: Step 1: Prepare fiber resin, grind wheat straw for 25 to 35 minutes, mix with 20% by mass sodium hydroxide solution, heat to 65 to 75°C, keep warm and soak for 60 to 80 minutes, add malic acid solution and mix, collect filter residue to obtain modified fiber resin, and set aside; Step 2: preparing a modified montmorillonite solution, mixing montmorillonite and distilled water, stirring for 1 to 2 hours, adding 3% to 5% of dodecyltrimethylammonium bromide by mass of montmorillonite, and then adding sodium dodecyl sulfate, stirring to obtain a modified montmorillonite solution for later use; Step 3: Mixing reaction, pour the fiber resin and modified montmorillonite solution into a reactor with a stirrer, heat to 100 to 120°C, stir and react for 45 to 55 minutes, and discharge the material to obtain the aging-resistant water-based adhesive.
[0031] In the specific preparation of the modified fiber resin, the mixing mass ratio of the crushed wheat straw and the sodium hydroxide solution with a mass fraction of 20% is 1:6.
[0032] The high temperature and high pressure cooking temperature in the modified fiber resin is 185-195°C, the pressure is 1.9-2.1MPa, and the mixing mass ratio of the alkali leaching material and the malic acid solution is 1:8; The mixed mass ratio of the filter residue in the modified fiber resin, phenol and 5% sodium hydroxide solution is 3:2:9.
[0033] Through the above-mentioned ratio, the preparation of the aging-resistant water-based glue in Example 2 and the comparative example has the following advantages: dodecyltrimethylammonium bromide has good solubility, heat resistance and surface activity, and dodecyltrimethylammonium bromide is mixed with carrageenan to form a uniform and tight network structure in the water-based glue, which effectively improves the sealing performance of the water-based glue, so that the prepared water-based glue can further increase the sealing performance of the water-based glue while ensuring good compatibility.
[0034] Example 3 Please refer to Figure 1As shown: A method for preparing an aging-resistant water-based adhesive and its application, comprising the following steps: Step 1: Prepare fiber resin, grind wheat straw for 25 to 35 minutes, mix with 20% by mass sodium hydroxide solution, heat to 65 to 75°C, keep warm and soak for 60 to 80 minutes, add malic acid solution and mix, collect filter residue to obtain modified fiber resin, and set aside; Step 2: preparing a montmorillonite solution, mixing montmorillonite and distilled water, stirring for 1 to 2 hours, adding 3% to 5% of the mass of montmorillonite hexadecyltrimethylammonium bromide, stirring to obtain a montmorillonite solution for later use; Step 3: Mixing reaction, pour the fiber resin and montmorillonite solution into a reactor with a stirrer, heat to 100 to 120°C, pour in tannic acid and chitosan, stir and react for 45 to 55 minutes, and discharge the material to obtain aging-resistant water-based adhesive.
[0035] The mixing mass ratio of dodecyltrimethylammonium bromide and sodium dodecyl sulfate in the modified montmorillonite solution is 1 to 1.2:1.1 to 1.3.
[0036] The weight proportions of the components of the aging-resistant water-based adhesive are as follows: modified fiber resin 20% to 40%, modified montmorillonite solution 20% to 40%, sodium hydroxide solution 6% to 10%, malic acid solution 3% to 6%, modified material 2% to 8%, dodecyltrimethylammonium bromide 0.5% to 3%, sodium dodecyl sulfate 1% to 3%, tannic acid 0.1% to 2%, and chitosan 0.1% to 2%.
[0037] Through the above-mentioned ratio, the preparation of the aging-resistant water-based glue in Example 3 and the comparative example has the following advantages: when carrageenan is used in combination with tannic acid, the rapid curing effect of the water-based glue is increased, and by combining tannic acid with chitosan, the prepared water-based glue can increase the curing speed of the glue more quickly, so that the drying time of the water-based glue will not increase significantly in a high humidity or low temperature environment. At the same time, the long-term durability of the glue is enhanced, and the elasticity and fatigue resistance of the water-based glue are improved. This combination method also improves the stability of the glue, so that it can maintain good bonding properties under various environmental conditions, especially in a humid or underwater environment.
[0038] Comparative Example 1 The environmentally friendly water-based adhesive provided in this comparative example is substantially the same as that in Example 1, the main difference is that in Example 1, a modified fiber resin is prepared and a modified material is added.
[0039] Comparative Example 2 The environmentally friendly water-based adhesive provided in this comparative example is substantially the same as that in Example 2, the main difference being that in Example 2, a modified montmorillonite solution is prepared, and dodecyltrimethylammonium bromide and sodium dodecyl sulfate are added.
[0040] Comparative Example 3 The environmentally friendly water-based adhesive provided in this comparative example is substantially the same as that in Example 3, the main difference is that in Example 3, the modified fiber resin and the modified montmorillonite solution are mixed, and tannic acid and chitosan are added.
[0041] The test results of water resistance, sealing and durability are shown in Table 1 below: Table 1: Tests on alkali content, compatibility and durability:
[0042] It can be seen from the test results in the above table that the aging-resistant water-based glue prepared in Example 1, Example 2 and Example 3, compared with the comparative example, adds calcium chloride, which improves the water stability of the sodium alginate-based material and further improves the water resistance of the water-based glue. The prepared water-based glue can further increase the sealing of the water-based glue while ensuring good compatibility, so that the prepared water-based glue can increase the curing speed of the glue more quickly, while enhancing the long-term durability of the glue.
[0043] The present invention provides a method for preparing an aging-resistant water-based adhesive and its application. In operation, the method comprises the following steps: firstly crushing wheat straw for 25 to 35 minutes, mixing the mixture with a sodium hydroxide solution having a mass fraction of 20%, heating the mixture to a temperature of 65 to 75°C, and soaking the mixture for 60 to 80 minutes. After adding a malic acid solution and mixing the mixture, collecting the filter residue, adding a modified material, obtaining a modified fiber resin, and setting the resin aside. The wheat straw is mixed with sodium alginate, and calcium chloride is added after the mixture, so that the polymer component in the prepared water-based adhesive can significantly increase the water resistance of the water-based adhesive through the combination of the wheat straw and the sodium alginate after contacting water, thereby preventing the water-based adhesive from becoming soft after contacting water. The water-based adhesive can be used in humid environments or in contact with water. Calcium chloride is added to improve the water stability of the sodium alginate-based material, further improving the water resistance of the water-based adhesive and extending the service life of the water-based adhesive. Montmorillonite and distilled water are mixed and stirred for 1 to 2 hours. 3% to 5% of the mass of montmorillonite is added with dodecyltrimethylammonium bromide, and then sodium dodecyl sulfate is added. After stirring, a modified montmorillonite solution is obtained for later use. Dodecyltrimethylammonium bromide is mixed with sodium dodecyl sulfate, and dodecyltrimethylammonium bromide is added. The invention has good solubility, heat resistance and surface activity. At the same time, dodecyl trimethyl ammonium bromide is mixed with carrageenan to form a uniform and tight network structure in the water-based glue, which effectively improves the sealing performance of the water-based glue, so that the prepared water-based glue can further increase the sealing performance of the water-based glue while ensuring good compatibility, and improve the waterproof and air-proof effect of the water-based glue; the modified fiber resin and the modified montmorillonite solution are poured into a reactor with a stirrer, heated to 100 to 120°C, tannic acid and chitosan are poured in, stirred for reaction for 45 to 55 minutes, and the material is discharged to obtain an aging-resistant water-based glue; the carrageenan and the mononitrate are mixed and stirred for 45 to 55 minutes, and the aging-resistant water-based glue is obtained. When tannic acid is used in combination, the rapid curing effect of the water-based glue is increased, and through the combination of tannic acid and chitosan, the prepared water-based glue can increase the curing speed of the glue more quickly, so that the drying time of the water-based glue will not increase significantly in high humidity or low temperature environments. At the same time, the long-term durability of the glue is enhanced, and the elasticity and fatigue resistance of the water-based glue are improved. This combination also improves the stability of the glue, so that it can maintain good bonding properties under various environmental conditions, especially in humid or underwater environments. This feature can reduce the limitations of the application of water-based glue in certain production processes that require rapid processing.
[0044] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing an aging-resistant water-based adhesive, characterized in that: The preparation method is specifically: Step 1: Prepare modified fiber resin, grind wheat straw for 25 to 35 minutes, mix with 20% by mass sodium hydroxide solution, heat to 65 to 75°C, keep warm and soak for 60 to 80 minutes, add malic acid solution and mix, collect filter residue, add modified material, obtain modified fiber resin, and set aside; Step 2: preparing a modified montmorillonite solution, mixing montmorillonite and distilled water, stirring for 1 to 2 hours, adding 3% to 5% of dodecyltrimethylammonium bromide by mass of montmorillonite, and then adding sodium dodecyl sulfate, stirring to obtain a modified montmorillonite solution for later use; Step 3: Mixing reaction, pour the modified fiber resin and modified montmorillonite solution into a reactor with a stirrer, heat to 100 to 120°C, pour in tannic acid and chitosan, stir and react for 45 to 55 minutes, and discharge the material to obtain aging-resistant water-based adhesive.
2. The preparation method according to claim 1, characterized in that: The specific preparation method of the modified fiber resin is: (1) After washing the wheat straw with distilled water for 1 to 2 times, the wheat straw is put into a grinder and ground for 25 to 35 minutes to obtain a wheat straw grind. The wheat straw grind is mixed with a sodium hydroxide solution having a mass fraction of 20%, and the mixture is put into a reactor, heated to 65 to 75° C., and soaked for 60 to 80 minutes to obtain an alkali-soaked product. (2) mixing the alkali-leached product with 8% malic acid solution by mass, placing the product in a high-temperature and high-pressure cooking tank, cooking the product for 2 to 3 hours, discharging the product, filtering the product, removing the filtrate, and collecting the residue; (3) The filter residue, phenol and 6% by mass sodium hydroxide solution are mixed and placed in a vacuum distillation apparatus for 50 to 60 minutes of vacuum distillation. 1% to 3% of a modified material is added to obtain a modified fiber resin.
3. The preparation method according to claim 1, characterized in that: The modified materials are sodium alginate solution and calcium chloride, and the weight ratio of the sodium alginate solution, calcium chloride and wheat straw is 3: (0.1 to 0.5):
1.
4. The preparation method according to claim 1, characterized in that: The specific steps of preparing the modified montmorillonite solution are as follows: Step 1, stirring at a constant temperature for 1 to 2 hours, and adding 3% to 5% of the mass of montmorillonite dodecyltrimethylammonium bromide during the stirring process, and then adding sodium dodecyl sulfate. After the stirring is completed, standing for 4 to 5 hours to obtain a mixed solution; Step 2: Filter the mixed solution, remove the filtrate, collect the filter residue, rinse the filter residue with distilled water for 2 to 3 times, filter under reduced pressure, collect the filtered filter residue, put the filtered filter residue into an oven and dry it to constant weight, then put it into a grinder and grind it for 30 to 40 minutes. After grinding, sieve it to obtain a modified montmorillonite solution.
5. The preparation method according to claim 1, characterized in that: The mixed mass ratio of the modified fiber resin and the modified montmorillonite solution is 2:
1.
6. The preparation method according to claim 1, characterized in that: In the specific preparation of the modified fiber resin, the mixing mass ratio of the crushed wheat straw and the sodium hydroxide solution with a mass fraction of 20% is 1:
6.
7. The preparation method according to claim 1, characterized in that: The high temperature and high pressure cooking temperature in the modified fiber resin is 185-195°C, the pressure is 1.9-2.1MPa, and the mass ratio of the alkali leaching material to the malic acid solution is 1:8; The mixed mass ratio of the filter residue, phenol and 5% sodium hydroxide solution in the modified fiber resin is 3:2:
9.
8. The preparation method according to claim 1, characterized in that: The mixed mass ratio of dodecyltrimethylammonium bromide and sodium dodecyl sulfate in the modified montmorillonite solution is 1 to 1.2:1.1 to 1.
3.
9. The preparation method according to claim 1, characterized in that: The weight ratio of each component of the aging-resistant water-based adhesive is composed of the following: 20% to 40% of modified fiber resin, 20% to 40% of modified montmorillonite solution, 6% to 10% of sodium hydroxide solution, 3% to 6% of malic acid solution, 2% to 8% of modified material, 0.5% to 3% of dodecyltrimethylammonium bromide, 1% to 3% of sodium dodecyl sulfate, 0.1% to 2% of tannic acid, and 0.1% to 2% of chitosan.
10. The aging-resistant water-based adhesive prepared according to the method of claims 1 to 9 is used for bonding polyurethane semi-rigid foam, polypropylene sheet, sponge cloth, non-woven cloth, PVC cloth, leather or synthetic leather.
Citation Information
Patent Citations
Preparation method of aging-resistant sealant
CN109897582A
